Pengaruh Pendekatan Inquiri Terbimbing MelaluiStadterhadap Hasil Belajar Siswa Mts Negeri SurakartaI Pada Mata Pelajaran Ipa Tahun Pelajaran 2015/2016 - Apriani, Meika; , Drs Djumadi M.Kes (2016)
The aim of this research is to know how the influence of inquiry approach that combined with STAD (Student Team Achievment Division) learning strategies to learning outcomes cognitif or vallue of study IPA. This research was held at MTs Negeri Surakarta I on VII C class as experiment class, VII A class as control class, on materyenergi of life. This research using true experiment methodh with simple random sampling. Instrumental tes with multiple choice test. The result of reaseach showed any influence or effect on learning outcomes between experiment class and control class. The result base on analisys of hypthesis with independent t test. Base on it hypothesis analisys, the value of probability is 0 and significant value 0,05. Therefore, probability value < significant value, so that null hypothesis (Ho) was rejected or not acceptable. The result of research also showed that combining of inquiry approach with strategies learning STAD is better than convensional method. That can see on average vallue, between experiment class and control class. Experiment class that use strategi learning Inquiry-STAD have average vallue 85,5 and control class that use convensional method have average vallue 77,25. The conclusion of this research is any influence or effect using inquiry approach that combine with STAD learning strategies outcomes sains student, shcool year 2015/2016 in MTs Negeri Surakarta I.